Exploring the factor explaining the continuity of hospital accreditation standard adoption in Indonesia - Viera Wardhani; Sutoto; Tjahjono Kuntjoro; Adi Utarini (Komisi Akreditasi Rumah Sakit (KARS), 2023)
Background: Hospital accreditation has been widely adopted to stimulate continuous quality improvement. Hence, understanding the factors that determine hospital capability to continuously maintain its accreditation status is critical.. Objective: This study aimed to explore the continuity of hospital accreditation status and its association with hospital characteristics and geographical disparities Methods: A three-year cohort of accredited hospitals in the year 2012-2014 was used. Hospital accreditation status, reaccreditation status at three years post accreditation (2015-2017) and their timeliness and improvement of accreditation status were recorded from the hospital accreditation report managed by the Indonesian Commission on Accreditation of Hospitals. Cross-tabulation of the outcome variables with hospitals characteristics (classification, ownership, specialty) and geographical area was performed, followed by a multiple logistic regression analysis to investigate determinants of the reaccreditation Results: Of the 461 hospitals accredited in the year 2012-2014, only 73% undertook the reaccreditation survey. At reaccreditation, 27% of the hospitals were reaccredited timely and 65% showed improved accreditation status. Higher hospital class, general hospitals, public hospitals, and their location in Java-Bali islands tended to have higher proportion of timely accreditation and improved accreditation status at reaccreditation. The logistic regression analysis confirmed that hospital class and those located in Java-Bali were significant determinants for continuity of hospital accreditation status. Conclusions: The low proportion of hospitals with continuous accreditation status within three years reaccreditation cycle is influenced by the hospital classification and provincial gap. This study suggested a step-wise quality regulation strategy focusing on developing a continuous quality improvement culture.